(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
The paper aimed to measure the impact of total banking risks and indicate the extent of their impact on economic stability for the period 2004-2021 using the bounds test. Two independent variables were identified to represent banking risks, namely (the ratio of non-performing loans to the total loans, the ratio of non-performing loans to the total capital), as well as Choosing some macroeconomic stability indicators as dependent variables: (bank capital, inflation, net trade balance ratio, net budget ratio, foreign reserves, banking concentration, standard of living). By increasing inflation rates, there is a negative impact of non-performing loans on the total loans and banking spread, as the high default rate of loans leads to a decline in the rate of banking prevalence, and there is a negative impact of non-performing loans on the total loans on the standard of living, as the high default rate of loans leads to To a decline in the average standard of living as a result of not granting loans to the population, and the research recommended that a study of the case of borrowers be considered before granting credit in order to reduce the default rate in loans by providing some guarantees to the banker, the need to use the indicator of the ratio of non-performing loans to total capital as one of the risks Banking that has an impact on the financial soundness of the bank, through what the sum of non-performing loans represents to the capital owned by the bank, and thus gives a clear vision of the capital owned by the bank